PENGARUH ARUS KAS OPERASI, PROFITABILITAS, DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMODERASI - Yoewono, Harsono; Roziq, Mohammad (Universitas Multimedia Nusantara, 2024)
Abstract - This research aims to evaluate the impact of operational cash flow, profitability, and leverage on earnings management, by considering institutional ownership as a moderating factor. The data used in this analysis was obtained from financial reports periodically published on the IDX from 2020 to 2022. Financial reports are data that is collected. This information comes from the official IDX website. Consumer goods companies listed on the IDX for 2020–2022 are the population considered in this analysis. Regression analysis was carried out in this research using Eviews 10 software. The findings of this analysis state that operating cash flow has a negative effect on earnings management, profitability has a positive effect on earnings management, leverage has no effect on earnings management, institutional ownership cannot moderate the effect of operating cash flow on earnings management, institutional ownership cannot moderate the effect of profitability on earnings management, institutional ownership can moderate the effect of leverage on earnings management. Keywords: Operating Cash Flow; Profitability; Leverage; Profit Management; Institutional Ownership